Silica aerogel characterization for the ePIC dRICH detector - Altamura Anna Rita (EPJ Web of Conferences)
The ePIC detector is specifically designed to address the entire physics program at the Electron-Ion Collider (EIC) and features several subdetectors, including the dual-radiator Ring Imaging Cherenkov (dRICH) detector for high-momentum particle identification. Silica aerogel is chosen as the solid radiator due to its crucial optical properties. Ongoing research aims to optimize these characteristics, focusing on the transmittance measurements of aerogel tiles with varying refractive indices and the associated measurement setup.